Postdigital Cybernetics - Donner, Martin; Allert, Heidrun (Encyclopedia of Postdigital Science and Education, 2025)
This article describes the development and reception of cybernetics from its beginnings in the 1940s. It moves through second-order cybernetics, which corresponds with the social liberalization of the 1960s and 1970s, to third-order cybernetics, which takes shape with the global intensification of ecological problems after the turn of the millennium. The article points at cybernetics as an important precursor of postdigital theory and outlines the main features of postdigital cybernetics, its main challenges, and future research direction